The Impact of Organizational Support and Ethical Climate On Turnover Intention: Job Satisfaction as a Mediator - Nassani, Abdelmohsen; Aljarallah, Khaled; Alsubaie, Shaye; Suwaidan, Hassan (The Arab Journal of Administration, 2023)
An ethical climate and organizational support are among the most significant determinants of the effectiveness of an organization’s operations. This study intends to analyze the influence of ethical climate and organizational support on the turnover intention with the mediating role of job satisfaction. The data was collected through a questionnaire distributed to employees working in the Kingdom of Saudi Arabia in both public and private sectors. A sample of 274 employees was obtained and analyzed using IBM SPSS Statistics 26 and the path analysis was conducted through Amos 23. The results showed that both perceived organizational support and ethical climate have a positive effect on job satisfaction. In addition, there is a negative relationship between job satisfaction and workers’ turnover intention. The research also argues that job satisfaction acts as a mediating factor between turnover intention and both factors of organizational support and ethical climate. This research differs from previous studies in that its model has not been previously investigated in the Saudi work environment. The study provides managers with relevant recommendations on approaches to increase job satisfaction and reduce turnover intention using some human resource management practices which are increasing ethical climate and ensuring organizational support. Therefore, it contributes to the